A Schiff Base-Derived Copper (II) Complex Is a Potent Inducer of Apoptosis in Colon Cancer Cells by Activating the Intrinsic Pathway - Maryam Hajrezaie; Mohammadjavad Paydar; Soheil Zorofchian Moghadamtousi; Pouya Hassandarvish; Nura Suleiman Gwaram; Maryam Zahedifard; Elham Rouhollahi; Hamed Karimian; Chung Yeng Looi; Hapipah Mohd Ali; Nazia Abdul Majid; Mahmood Ameen Abdulla (The Scientific World Journal)
Metal-based drugs with extensive clinical applications hold great promise for the development of cancer chemotherapeutic agents. In the last few decades, Schiff bases and their complexes have become well known for their extensive biological potential. In the present study, we examined the antiproliferative effect of a copper (II) complex on HT-29 colon cancer cells. The Cu(BrHAP)2 Schiff base compound demonstrated a potent antiproliferative effect in HT-29 cells, with an IC50 value of 2.87 μg/ml after 72 h of treatment. HT-29 cells treated with Cu (II) complexes underwent apoptosis death, as exhibited by a progressive elevation in the proportion of the G1 cell population. At a concentration of 6.25 μg/ml, the Cu(BrHAP)2 compound caused significant elevation in ROS production following perturbation of mitochondrial membrane potential and cytochrome c release, as assessed by the measurement of fluorescence intensity in stained cells. Furthermore, the activation of caspases 3/7 and 9 was part of the Cu (II) complex-induced apoptosis, which confirmed the involvement of mitochondrial-mediated apoptosis. Meanwhile, there was no significant activation of caspase-8. Taken together, these results imply that the Cu(BrHAP)2 compound is a potential candidate for further in vivo and clinical colon cancer studies to develop novel chemotherapeutic agents derived from metal-based agents.